River in Banjarese Culture at Chronicle of Banjarmasin - Dewi Alfianti Tifani (International Journal of Southeast Asian Studies (IJSAS), 2022)
In Banjar society, the river is a substantive cultural setting that reconstructs Banjar. Hikayat Banjar itself is one of the texts that is a reference to the depiction of the early identity of Banjar. Through the study of literary anthropology, it can be known in the Tale of Banjar that the river is part of the existential change system of the three kingdoms, the Dipa State, the Daha State, and the Banjar Kingdom. Rivers also became part of a religious system that transcendentally had the functions of creation, healing, and oblivion of figures in the royal power structure. The river is also part of a political and governmental system in which an understanding of the water-based fleet (river and sea) makes it a force to conquer the territories around the kingdom, establish diplomatic relations with China, as well as as part of a security defense system in the war between the rulers of the Daha State and the rulers of the Banjar Kingdom.